(untitled) (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: To clarify the current situation of the international dissemination of Taijiquan culture under the background of "Belt and Road", as well as the main content and the influencing factors of the international communication. As one of the excellent traditional cultural projects in China, Taijiquan culture has made its development with broad stage characteristics. For a long time, Taijiquan culture has played a significant and important role in national foreign cultural exchanges. In recent years, through the communication of "Confucius Institute" at the national level and various "Belt and Road" and folk Taijiquan cultural performances, Taijiquan culture has successfully been spread around the world, and has been recognized and loved by the people of the world. To enrich the world The diversity of boundary cultures and the mutual understanding of various peoples have made important contributions. Ji globalization has become an irreversible trend of The Times in the development of today’s world. With economic globalization is the development of "soft power" such as culture and ideology. Cultural soft power is undoubtedly an important part of the national soft power. Taijiquan culture is regarded as a special sports form closely combining the great rejuvenation of the Chinese nation. Since the 18th National Congress of the Communist Party of China, the concept of "vigorously carrying forward traditional national culture", "firm cultural confidence", "reviving traditional culture" and so has become the guidance of the new era. From the historical experience, the culture of a nation from Letter, rejuvenation and promotion cannot be separated from the innovative inheritance and external dissemination of its national culture. International communication of culture needs unimpeded channels. In 2013, General Secretary Xi Jinping proposed a cooperation initiative on building the Silk Road Economic Belt and the 21st Century Maritime Silk Road, hereinafter referred to as "Belt and Road". With the implementation of the strategy, its international influence and value effects are increasingly prominent in politics, economy and culture. "Belt and Road" will provide a good strategic opportunity for the international development of Chinese Taijiquan culture. Taijiquan culture will usher in the country with the implementation of the "Belt and Road" strategy and the deepening of economic and cultural exchanges between countries along the Belt and Road New opportunities for international development. The overseas exchange of the whole folk Taijiquan culture is showing a thriving scene. The increasingly frequent international exchange of folk Taijiquan culture has promoted the internationalization process of Taijiquan culture, made Taijiquan culture a cultural system with world influence, and promoted the specific implementation of Chinese culture in going global. Methods: It mainly uses the literature method, expert interview method and logic analysis method and the strategic background of the "Belt and Road". Document method, with "Taijiquan culture", "national traditional sports" and "Belt and Road" as the key words searched in China CNKI and Anqing Normal University Library, retrieved 563 documents from 2011-2021. Through screening and screening, 10 documents, 2 works study Taijiquan cultural reference basis and provide theoretical support and to ensure the authenticity and accuracy of the documents. Dedicated to it At-home interview method interviews experts and scholars face to face in the Taijiquan field or by telephone, and seek guidance on the specific issues of Taijiquan culture. Based on the historical characteristics and cultural attributes of Taijiquan culture, it promotes the dissemination and coupling of Taijiquan culture internationalization, and investigates the reality of the internationalization of Taijiquan culture under the background of "One Belt And One Road". Results: Taijiquan traditional sports culture embodies the spiritual heritage and national value pursuit in China, it is rooted in the tradition, and with the development of The Times and refining the new ideas of The Times, both has the development of The Times needs to build needs, and in line with the realistic path of the development of characteristic socialism. The combination of Taijiquan culture with the international dissemination of "One Belt And One Road" is conducive to the coordination and integration of traditional culture and sports culture in the process of the 14th Five-Year Plan period, and helps to promote the development of Taijiquan culture in the trend of globalization. At the present stage, the background of "One Belt And One Road" strategy provides for the transmission of Taijiquan culture with the carrier, Taijiquan culture provides an opportunity for international cultural exchanges, and Taijiquan culture has a high say in the communication. Analyze the motivation of Taijiquan culture to provide a serious and grand historical vision. The international dissemination and development of Taijiquan culture has injected the national cultural concept and will into it. The strategic layout of "One Belt And One Road" and the historical teaching and experience of Taijiquan culture have carried forward the national concept and national culture, and promoted the humanistic concept and scientific spirit of China’s Taijiquan culture. Under the context of "One Belt And One Road", the dilemma of international transmission of Taijiquan culture country mainly has the following 5 points: cultural innovation and communication mode are relatively lagging behind The level of cultural exchanges and governance needs to be improved, the cultural communication force needs to be strengthened, and most countries along the Belt and Road remain vigilant about Chinese culture. First, Taijiquan culture self-killing: the "loss of self" of Taijiquan culture. Second, Chinese culture misinterpretation: the "regional difference" of Taijiquan culture. Third, the transmission mode lags behind: the "lack of carriers" of Taijiquan culture. Fourth, the rigid communication means: the "lack of symbols" of Taijiquan culture. Fifth, the communication power needs to be strengthened: the "memory shortage" of Taijiquan culture. Conclusion: "One Belt And One Road", as an important way to participate in the process of globalization, the cultural dissemination of Taijiquan cultural tradition needs to think about how to implement strategic coordination under the influence of various strong cultures and strong media, form strategic synergy, expand communication channels and enhance the international discourse power. Therefore, the paper for the background of "area" the reality of taijiquan culture international communication dilemma, then put forward: first, cultivate the national traditional sports culture consciousness, construct cross-cultural communication content system, spread the taijiquan culture and traditional sports culture, create international communication card, enhance cultural affinity and cross-border national cultural identity. Second, Face up to the cultural differences of "One Belt And One Road" countries, build a differentiated communication mode, spread the Chinese nation culture, and enrich the spiritual and cultural life. Third, the construction of three-dimensional communication means and enhance the discourse power of cross-cultural communication are conducive to the realization of the beautiful vision of peace and open mind of all countries. Fourth, improve the cultural skills of Taijiquan and promote the dissemination of "wisdom". Fifth, excavate the cultural memory resources of Taijiquan, and build a cultural sharing system.